2006
DOI: 10.1007/s11109-006-9010-9
|View full text |Cite
|
Sign up to set email alerts
|

What They Do Does Matter: Incumbent Resource Allocations and the Individual House Vote

Abstract: It is reasonable to presume that House incumbents through their behaviors and resource allocations (e.g., trips home, staff, etc.) are responsible for their electoral success. The empirical case for the resource allocation hypothesis, however, rests primarily upon the support of a few experimental design studies. The remainder of the evidence from 25 years of tests of this hypothesis, at the district and individual-levels, is littered with null findings. Scholars suggest two methodological obstructions hinder … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 41 publications
0
4
0
1
Order By: Relevance
“…Typical explanations for why candidates already in office get more votes are institutional: incumbents have access to more resources (Abramowitz, 1991) and can provide goods and services to constituents in exchange for support (Cain, Ferejohn, & Fiorina, 1987;Romero, 2006). They can also take credit for successes, capitalize on polls and publicity (Mayhew, 1974), and learn from experience more generally (Campbell, 2008).…”
Section: Incumbency Effectsmentioning
confidence: 99%
“…Typical explanations for why candidates already in office get more votes are institutional: incumbents have access to more resources (Abramowitz, 1991) and can provide goods and services to constituents in exchange for support (Cain, Ferejohn, & Fiorina, 1987;Romero, 2006). They can also take credit for successes, capitalize on polls and publicity (Mayhew, 1974), and learn from experience more generally (Campbell, 2008).…”
Section: Incumbency Effectsmentioning
confidence: 99%
“…Supported by his seminal findings, a large body of future works (e.g. Abramowitz, 1975; Ferejohn, 1977; Fiorina, 1977; Mann and Wolfinger, 1980; Coates, 1995; Cox and Katz, 1996; Herrera and Yawn, 1999) has taken the existence of the incumbency advantage and its growth for granted and shifted the attention to its possible explanations, such as the growth of bureaucracy (Fiorina, 1977), the change in relations between incumbents and constituents (Fenno, 1978; Romero, 2006) or the influence of the media (Prior, 2006).…”
Section: The Growth Of the Incumbency Advantage: Consequences Of A Pamentioning
confidence: 99%
“…Fiorina (1981b) argued that previous election outcomes might influence how much mail members choose to send to their constituents or how many offices they decide to open in the district. In an innovative bit of research, Romero (2006) showed that the simultaneity concerns raised by Fiorina are important and that, once these effects are controlled, the use of official resources has a demonstrably positive effect on the probability that respondents support the incumbent member of Congress. Rejecting the direct-effects approach, Cain, Ferejohn, and Fiorina (1987) argued that the activities of members affect how constituents perceive the members.…”
Section: Hypothesesmentioning
confidence: 99%